Quality assurance for school health service providers at primary healthcare centers in Hillah (Iraq) - Al-Taee, Mahdi Hamzah; Hajwal, Salim K.; Ayad, Zahraa M.; Muhaibes, Fakhria Jaber; Khaleel, Muna Abdulwahab; Hassan, Abbas Abdul-Hussein; Abbas, Alaa Hamza; Ridha-Salman, Hayder; Abbas, Zahraa H. (Pharmakeftiki, 2025)
This study aimed at evaluating the performance of school health providers at primary health centers in Al-Hilla City (Hillah) through the application of a quality assurance framework. A descriptive evaluation study was conducted from October 5, 2024 to March 25, 2025. A purposive sample of 63 individuals was selected using a non-probability sampling technique from 15 primary healthcare centers, drawn from two health sectors within the Al-Hilla City Center under the Babylon Health Directorate in Iraq. The sample comprised 20 members of the medical staff and 43 members of the nursing staff. A panel of thirteen experts participated in a pilot study in order to assess the reliability of the evaluation instrument through content validity and internal consistency metrics. The findings indicate a growing demand and a diminishing supply of workforce in primary health care. The quality assurance assessment of school health activities performed by medical and nursing staff revealed a fair overall performance. However, health education services provided to teaching staff and students were found to be suboptimal.